2002
DOI: 10.1093/emboj/21.6.1267
|View full text |Cite
|
Sign up to set email alerts
|

TheANGUSTIFOLIAgene ofArabidopsis, a plantCtBPgene, regulates leaf-cell expansion, the arrangement of cortical microtubules in leaf cells and expression of a gene involved in cell-wall formation

Abstract: We previously showed that the ANGUSTIFOLIA (AN) gene regulates the width of leaves of Arabidopsis thaliana, by controlling the polar elongation of leaf cells. In the present study, we found that the abnormal arrangement of cortical microtubules (MTs) in an leaf cells appeared to account entirely for the abnormal shape of the cells. It suggested that the AN gene might regulate the polarity of cell growth by controlling the arrangement of cortical MTs. We cloned the AN gene using a map-based strategy and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
265
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(286 citation statements)
references
References 77 publications
17
265
2
2
Order By: Relevance
“…This scenario would suggest that the selection must occur in the heterozygous state and the question arises whether dosage dependent regulators are also involved with this type of quantitative response. Examples of single gene heterosis were reported many years ago (34) and now that the molecular basis of these loci has been defined, an example of a transcription factor and a signal transduction component are represented (35,36). This sample of course is too small to form any generalizations, but it is consistent with other studies of the molecular basis of QTL and dosage dependent regulators.…”
Section: Is There An Involvement In Hybrid Vigor?supporting
confidence: 76%
“…This scenario would suggest that the selection must occur in the heterozygous state and the question arises whether dosage dependent regulators are also involved with this type of quantitative response. Examples of single gene heterosis were reported many years ago (34) and now that the molecular basis of these loci has been defined, an example of a transcription factor and a signal transduction component are represented (35,36). This sample of course is too small to form any generalizations, but it is consistent with other studies of the molecular basis of QTL and dosage dependent regulators.…”
Section: Is There An Involvement In Hybrid Vigor?supporting
confidence: 76%
“…This suggests that the AN1 protein may have a function in microtubule positioning and that a dense collar of cortical microtubules in an apical position is important for normal branching (Szymanski, 2009). The AN1 gene encodes the plant homolog of CtBP/BARS and was postulated to function in vesicle budding from the Golgi (Folkers et al, 2002;Kim et al, 2002;Corda et al, 2006;Stern et al, 2007;Bai et al, 2010). Apart from this correlative evidence that the cortical microtubule collar seen in young trichome stalks is required for branching (Folkers et al, 2002), we have little understanding of the microtubule configurations of the exact branch point before and at branching, nor is it known how microtubule arrays are formed and established on the new branch (Beilstein and Szymanski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In order to deepen our understanding of microtubule function during branching, we analyzed double mutants of tor2 with an1. The AN1 protein is believed to have a microtubulerelated function (Folkers et al, 2002;Kim et al, 2002), but it is unclear how this mutant responds to the specific alterations of microtubule dynamics. Finally, we were interested to understand the similarities and differences of trichome twisting in tor2 and dis1 background.…”
Section: Introductionmentioning
confidence: 99%
“…Organ size is determined by both cell size and cell number. Genetic studies have shown that differences in cell size or cell polar elongation apparently contribute to the size difference of plant organs (Kim et al, 1998(Kim et al, , 2002Kondorosi et al, 2000). On the other hand, larger organs tend to contain more cells than smaller organs, implying that cell division plays a fundamental role in organ size determination during organogenesis.…”
Section: Introductionmentioning
confidence: 99%